PENGARUH DEBT TO EQUITY RATIO DAN RETURN ON EQUITY TERHADAP PRICE TO BOOK VALUE PADA PT ASTRA INTERNATIONAL, Tbk PERIODE 2014 – 2023 - Andy Riyanto; Sri Mardiana (Journal of Research and Publication Innovation, 2025)
The purpose of this study is to determine the effect of Debt to Equity Ratio and Return On Equity on Price to Book Value at PT Astra International, Tbk both partially and simultaneously. The research method used is a quantitative method with an associative approach. The sample used is the Financial Report of PT Astra International, Tbk for 10 (ten) years which has been made into time series data. Data analysis in this study uses classical assumption tests, multiple linear regression analysis, hypothesis testing and determination coefficient analysis. The results of this study are multiple linear regression equations of Y = -1.892 + 0.046X1 - 0.028X2 + e. Partially, the Debt to Equity Ratio variable has a positive and significant effect on Price to Book Value with the results of tcount > ttable or (7.045 > 1.895) with a significance level of 0.00 < 0.05. Meanwhile, the Return On Equity variable has no significant effect on Price to Book Value with the result of tcount < ttable or (-1.079 <1.895) with a significance level of 0.316 > 0.05. Simultaneously, Debt to Equity Ratio and Return On Equity have a positive and significant effect on Price to Book Value with the value of Fcount > Ftable, namely (24.987 > 4.737) with a significance level of 0.001 < 0.05. The coefficient of determination is 84.2%, the remaining 15.8% is influenced by other variables and factors.